ANALISIS KEMAMPUAN BEBAN PAJAK TANGGUHAN DAN AKRUAL DALAM MEMPREDIKSI MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Tercatat Di Bursa Efek Indonesia) - Raeza Ayu Agustina, 10.05.52.0112; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2015)
The study was conducted to analyze the deferred tax expense and accruals in detecting earnings management in manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the year 2010-2012. Data used in the research originated from audited annual financial statements, the population of the study were 114 manufacturing companies listed on the Indonesia Stock Exchange with the object of study (sample) accounted for 38 companies were selected using purposive sampling method. Data were tested using logistic regression methods. These results indicate that the deferred tax expense no significant effect on the probability of earnings management firms do. Accrued no significant effect on the probability of earnings management firms do.Keywords: Deferred Tax Expense, Accrual, Earnings Management